Association between moderate-to-vigorous physical activity and attention among children aged 6–12 years: chain mediating effects of fundamental movement skills and aerobic fitness - Wu, Haitan; Wang, Xidong; Jin, Zhangyi (Frontiers in Pediatrics, 2024)
Purpose: To explore the association between physical activity and attention among children aged 6-12 years and to determine whether fundamental movement skills and aerobic fitness mediate the association between physical activity and attention. Methods: A total of 1086 schoolaged children (mean age: 9.40±2.03 years) were included in the present study. Physical activity was assessed using the International Physical Activity Scale-Short Form. Fundamental movement skills were assessed using the Test of Gross Motor Development, third edition, and aerobic fitness was evaluated using the 20-metre shuttle run. Attention was assessed by the d2 Attention Test. Results: There were significant positive correlations between physical activity and fundamental movement skills, physical activity and aerobic fitness, and physical activity and attention (all p<0.05). Both fundamental movement skills and aerobic fitness fully mediated the relationship between physical activity and attention. In addition, fundamental movement skills and aerobic fitness had chainmediating effects on the relationship between physical activity and attention. Conclusion: High levels of physical activity were positively associated with attention among school-aged children. Fundamental movement skills and aerobic fitness played a chain-mediating role in the relationship between physical activity and attention.